High-rate long-cycle-life battery positive electrode and preparation method thereof

By constructing fast ion conductors and carbon cladding on the surface of lithium iron phosphate particles, and using a composite foam aluminum current collector with a hierarchical structure, combining carbon nanotubes and lithium polyacrylate, the low conductivity and foam aluminum collection of lithium iron phosphate materials are solved. The problem of insufficient fluid stability has achieved a high-magnification and long cycle life of lithium-ion batteries.

CN119324203APending Publication Date: 2025-01-17贵州嘉尚新能源材料有限公司
0 Cites 2 Cited by

Patent Information

Application Number
CN202411357905.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing lithium-ion battery cathode material lithium iron phosphate has low electronic conductivity and ionic conductivity, resulting in poor low-temperature performance and rate performance. It is difficult for traditional carbon coating technology to achieve a uniform, dense and tight-bonded carbon layer, affecting electrochemistry. performance. At the same time, the existing foam aluminum current collector lacks mechanical strength and structural stability, which can easily lead to deformation and fracture, affecting battery performance and cycle life.

Method used

Using composite modification strategy, fast ion conductor cladding and carbon cladding are constructed on the surface of lithium iron phosphate particles, and composite foam aluminum current collector designed by hierarchical structures combines carbon nanotubes and lithium polyacrylate to optimize the conductive network and Structural stability improves the electron and ion transport performance of the material.

Benefits of technology

It significantly improves the ion and electron transport performance of lithium iron phosphate materials, extends the cycle life of the battery, improves the rate performance and energy density, and at the same time enhances the mechanical strength and structural stability of the current collector, avoiding deformation and fracture problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324203A_ABST
    Figure CN119324203A_ABST
Patent Text Reader

Abstract

The invention discloses a high-rate long-cycle-life battery positive electrode and a preparation method thereof. The positive electrode comprises a composite current collector and a positive electrode active material coating coated on at least one surface of the composite current collector, the positive electrode active material coating comprises a positive electrode active material, a carbon nanotube and lithium polyacrylate; the mass ratio of the positive electrode active material to the carbon nanotube to the lithium polyacrylate is (90-99.5): (0.2-5): (0.3-5), and the positive electrode active material comprises lithium iron phosphate particles, a fast ion conductor coating layer coating the outer surface of the lithium iron phosphate particles, and a carbon coating layer coating the outer surface of the fast ion conductor coating layer. Compared with the prior art, the battery positive electrode provided by the invention has the advantages of high rate and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a high-rate and long-cycle-life battery positive electrode and a preparation method thereof. Background Art

[0002] With the continuous development of modern society, people's demand for portable electronic devices, electric vehicles, etc. is growing. As one of the core components of these devices, lithium-ion batteries are favored due to their high energy density, long cycle life and excellent safety performance. Since their commercialization in the 1990s, lithium-ion batteries have become the mainstream choice for various consumer electronic products and new energy vehicles.

[0003] Among the various components of lithium-ion batteries, the positive electrode plays a vital role. The positive electrode usually includes a current collector and a positive electrode material layer disposed on the current collector. Its performance directly affects the capacity, rate performance and service life of the battery. At present, the mainstream positive electrode materials include layered oxides, spinel and olivine structures. Among them, lithium iron phosphate with olivine structure has become a research hotspot and the preferred material in the field of power batteries due to its rich raw material sources, low cost, environmental friendliness, high thermal stability and excellent cycle performance.

[0004] However, lithium iron phosphate also has some inherent defects, such as low electronic conductivity and ionic conductivity, which leads to unsatisfactory low-temperature performance and rate performance. In addition, the interfacial side reactions between lithium iron phosphate and the electrolyte will also aggravate the capacity decay and shorten the cycle life of the battery. In order to overcome these shortcomings, researchers have carried out a lot of modification work in order to improve the comprehensive electrochemical performance of lithium iron phosphate and meet the stringent requirements of the power battery field for low-temperature performance, fast charge and discharge capabilities and long cycle life.

[0005] Among the existing modification strategies, surface carbon coating is a common and effective method. By introducing a conductive carbon layer on the surface of lithium iron phosphate particles, the electronic conductivity of the material can be significantly improved and the charge transfer dynamics can be promoted. However, a single carbon coating modification is often difficult to achieve the desired effect, especially in improving the ion diffusion dynamics. In addition, traditional solid-phase carbon coating methods, such as mechanical mixing and high-temperature calcination, make it difficult to obtain a uniform and dense carbon layer that is tightly bonded to the matrix. This results in the inability to fully exert the role of the carbon coating layer and the modification effect is unsatisfactory.

[0006] In addition, an overly thick or uneven carbon coating may also have negative effects. Excessive carbon addition will reduce the energy density of the positive electrode material, while an uneven carbon layer may hinder ion transport, resulting in a decrease in electrochemical performance. Therefore, existing carbon coating technology still cannot meet the requirements of high-performance lithium-ion battery positive electrode materials.

[0007] In the face of these challenges, it is urgent to develop novel and efficient composite modification strategies that can improve the electronic conductivity of lithium iron phosphate materials while also improving their ion transport kinetics. The construction of composite materials with both high ion and high electron transport channels is expected to break through the limitations of a single modification method and comprehensively improve the electrochemical performance of lithium iron phosphate cathodes.

[0008] In addition, the current collector of the positive electrode acts as a carrier of active materials and an electron transmission channel, and its performance has an important influence on the energy density, rate performance and cycle stability of the battery. At present, aluminum foil is commonly used as the current collector material for the positive electrode of commercial lithium-ion batteries. However, the aluminum foil current collector has problems such as low specific surface area and limited active material loading, making it difficult to further improve the energy density of the battery. In order to solve this problem, the researchers proposed a design scheme using foamed aluminum as the positive electrode current collector.

[0009] However, the existing aluminum foam current collector generally adopts a single-layer uniform porosity and density design. While improving the specific surface area and conductivity, it often sacrifices the mechanical strength and structural stability of the current collector. It is easy to deform or break during battery assembly and charging and discharging, resulting in problems such as active material shedding and increased interface impedance, which seriously affects the performance and cycle life of the battery. In addition, the stress distribution of the single-layer aluminum foam current collector is uneven, and it is easy to be damaged in the stress concentration area, further reducing the mechanical stability and reliability of the current collector. Therefore, designing and preparing a current collector with high specific surface area, high conductivity, high mechanical strength and high structural stability is also crucial to improving the performance of the battery positive electrode.

[0010] In summary, in the field of lithium-ion battery positive electrodes, developing battery positive electrodes with high rate and long cycle life will be an important research direction and development trend. Summary of the invention

[0011] The main purpose of the present invention is to provide a battery positive electrode with high rate and long cycle life in view of the shortcomings of the prior art.

[0012] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0013] A high-rate and long-cycle-life battery positive electrode comprises a composite current collector and a positive electrode active material coating coated on at least one surface of the composite current collector; the positive electrode active material coating comprises a positive electrode active material, carbon nanotubes and lithium polyacrylate; the mass ratio of the positive electrode active material, the carbon nanotubes and the lithium polyacrylate is (90~99.5):(0.2~5):(0.3~5), and the positive electrode active material comprises lithium iron phosphate particles, a fast ion conductor coating coated on the outer surface of the lithium iron phosphate particles, and a carbon coating coated on the outer surface of the fast ion conductor coating.

[0014] Preferably, the particle size of the positive electrode active material particles is 0.1-1.5 μm.

[0015] Preferably, the preparation method of the positive electrode active material is as follows:

[0016] 1) Mixing a raw material of a fast ion conductor with hydrogen peroxide, reflux at 50-60° C. for 5-10 hours, reflux at 70-90° C. for 1-5 hours, and reflux at 90-100° C. for 0.5-3 hours, then adding anhydrous ethanol, heating and reflux again to obtain a polyoxometalate; wherein the raw material of the fast ion conductor is a transition metal element and / or a transition metal compound;

[0017] 2) dispersing FePO4 in the polyoxometallic acid, drying and heat treating the FePO4 at a temperature of 300 to 600° C. for 2 to 6 hours to obtain FePO4 coated with a fast ion conductor;

[0018] 3) mixing the fast ion conductor coated FePO4, Li2CO3 and glucose in a mass ratio of (1-2):(4-6):(1-2), adding water, adjusting the solid content to 20%-40 wt %, and fully stirring and dispersing for 1-2 hours to obtain a mixed material;

[0019] 4) spray drying the mixed material in step 3), and adjusting the inlet temperature of the spray drying equipment to 200-240° C., the outlet temperature to 100-120° C., and the feed rate to 80 kg / h to obtain a dried material;

[0020] 5) The spray-dried material is loaded into a mold, compacted into blocks using a hydraulic press, loaded into a sagger, and then transferred to a push plate furnace for sintering;

[0021] 6) Heat up the push plate furnace first, pass nitrogen, reach the atmosphere requirement of less than 100ppm, push the sagger into the push plate furnace, and sinter according to the heating stage of 300~550℃, 4~6h; constant temperature stage of 750℃, 8~10h; cooling stage of 6~8h, and discharge;

[0022] 7) Grind the material fired in the push plate furnace to obtain a positive electrode active material with a particle size of 0.1~1.5μm.

[0023] Preferably, in step 1), the transition metal element is one or more of W, Mo, Ti, Nb, Ta and Ir; the transition metal compound is one or more of ammonium tungstate, ammonium metatungstate, tungstic acid, tungsten hexachloride, sodium tungstate dihydrate, ammonium molybdate, molybdenum hexachloride, sodium molybdate, tetrabutyl titanate, titanium tetraisopropoxide, titanium tetrachloride, niobium nitrate and niobium chloride.

[0024] Preferably, in step 1), the heating reflux temperature after adding anhydrous ethanol is 40 to 60° C., and the reflux time is 15 to 30 hours.

[0025] Preferably, in step 1), the mass fraction of the hydrogen peroxide is 10-30%; the mass ratio of the anhydrous ethanol to the hydrogen peroxide is 1:(0.5-2); and the mass ratio of the polyoxometallic acid to the positive electrode active material is (0.1-5):100.

[0026] Preferably, the composite current collector includes an aluminum foil layer and a composite aluminum foam layer arranged on the aluminum foil layer, the composite aluminum foam layer includes a first aluminum foam, a second aluminum foam and a third aluminum foam arranged in sequence from the inside to the outside, the density ρ1 of the first aluminum foam, the density ρ2 of the second aluminum foam and the density ρ3 of the third aluminum foam satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first aluminum foam, the porosity φ2 of the second aluminum foam and the porosity φ3 of the third aluminum foam satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first aluminum foam, the thickness h2 of the second aluminum foam and the thickness h3 of the third aluminum foam satisfy the relationship: h1<h2<h3.

[0027] Among them, the positive electrode of the present invention adopts a composite current collector of aluminum foil and composite foam aluminum. First, the composite foam aluminum layer has a high specific surface area and a three-dimensional network structure, which is not only conducive to the infiltration of the electrolyte, but also can load more active materials and is conducive to the uniform distribution of active materials, which can shorten the transmission path of electrons and ions, reduce the interface resistance, and improve the energy density and rate performance of the battery. Secondly, the composite foam aluminum with gradient density, porosity and thickness distribution of the present invention can realize the layer-by-layer transmission and buffering of stress, avoid stress concentration leading to local deformation, fracture or damage of the current collector, and improve the mechanical stability and reliability of the current collector. Thirdly, the composite foam aluminum with gradient density, porosity and thickness distribution of the present invention can not only significantly improve the specific surface area and conductivity of the current collector, but also take into account mechanical strength and structural stability, effectively solving the problem that the existing single-layer foam aluminum current collector is prone to deformation and fracture. In addition, the second and third layers of low-density and high-porosity aluminum foam can provide a larger specific surface area, which is beneficial to the loading of active materials and the infiltration of electrolyte, thereby improving the energy density and rate performance of the battery; while the first layer of aluminum foam has a relatively high density and low porosity, which can provide sufficient mechanical support and anti-deformation ability to ensure the structural integrity and stability of the composite current collector.

[0028] Preferably, the density ρ1 of the first foam aluminum is 0.5-0.9 g / cm³, the density ρ2 of the second foam aluminum is 0.3-0.5 g / cm³, and the density ρ3 of the third foam aluminum is 0.1-0.3 g / cm³; the porosity φ1 of the first foam aluminum is 50-70%, the porosity φ2 of the second foam aluminum is 70-85%, and the porosity φ3 of the third foam aluminum is 85-95%; the thickness h1 of the first foam aluminum is 0.5-1 μm, the thickness h2 of the second foam aluminum is 1-2 μm, and the thickness h3 of the third foam aluminum is 2-4 μm; the thickness h4 of the aluminum foil layer is 0.5-1 μm; and the total thickness of the composite current collector is 4-8 μm.

[0029] Preferably, the pore size d1 of the first foam aluminum, the pore size d2 of the second foam aluminum, and the pore size d3 of the third foam aluminum satisfy the relationship: d1<d2<d3; the pore size d1 of the first foam aluminum is 1~5μm, the pore size d2 of the second foam aluminum is 5~10μm, and the pore size d3 of the third foam aluminum is 10~15μm.

[0030] Preferably, the surface of the composite foam aluminum layer is further provided with a carbon nano coating, and the thickness of the carbon nano coating is 10-20 nm.

[0031] In addition, the present invention also provides a method for preparing the above-mentioned high-rate and long-cycle-life battery positive electrode, comprising the following steps:

[0032] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;

[0033] a. The first foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (15-25): 1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the aluminum powder is 0.1-0.4μm, and the particle size of the urea is 0.2-0.5μm;

[0034] b. The second foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the aluminum powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm;

[0035] c. The third foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the aluminum powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm;

[0036] 2) preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process;

[0037] 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer;

[0038] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried;

[0039] 5) Dispersing the positive electrode active material, carbon nanotubes and lithium polyacrylate in N-methylpyrrolidone in a mass ratio of (90-99.5):(0.2-5):(0.3-5), and stirring evenly to obtain a positive electrode active material coating slurry;

[0040] 6) coating the positive electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the battery positive electrode.

[0041] Preferably, step 4) further comprises surface modification of the composite current collector obtained after cooling, depositing a 10-20 nm thick carbon nanocoating, and hot rolling the surface modified composite current collector on a precision rolling mill at a rolling temperature of 100-150° C. and a rolling rate of 5-10%.

[0042] Compared with the prior art, the present invention has at least the following beneficial effects:

[0043] 1) The present invention constructs a fast ion conductor coating layer and a carbon coating layer on the surface of the lithium iron phosphate particles of the positive electrode; wherein, the electrochemical performance of the lithium iron phosphate material is mainly limited by its low electronic conductivity and ionic conductivity. After the introduction of the fast ion conductor coating layer, on the one hand, the fast ion conductor material itself has a high ionic conductivity, which can provide a fast transmission channel for lithium ions; on the other hand, an atomic-scale transition zone is formed at the interface between the fast ion conductor layer and the lithium iron phosphate particles, which is conducive to the rapid migration of lithium ions at the interface and reduces the interface impedance; in addition, the fast ion conductor coating layer can also effectively block the contact between the positive electrode material and the electrolyte, thereby greatly reducing the dissolution of the transition metal and the occurrence of side reactions between the electrode and the electrolyte. Therefore, the fast ion conductor coating layer can significantly improve the ionic conductivity of the lithium iron phosphate material, improve the rate performance and cycle performance. At the same time, the introduction of the carbon coating layer can improve the electronic conductivity of the material, accelerate the electron transfer kinetics, and improve the charge and discharge rate of the material. Therefore, the synergistic effect of the two coating layers can fundamentally overcome the problem of low conductivity of lithium iron phosphate and achieve a comprehensive improvement in electrochemical performance.

[0044] 2) The positive electrode active material coating of the present invention further optimizes the conductive network and structural stability of the material by adding carbon nanotubes and lithium polyacrylate to the positive electrode active material. Although fast ion conductor coating and carbon coating can significantly improve the intrinsic conductivity of lithium iron phosphate materials, in actual electrodes, the contact resistance between active material particles will still limit electron transfer, resulting in poor overall conductivity of the electrode. After the introduction of carbon nanotubes, a conductive network can be formed between the active material particles, providing an efficient electron transfer channel, reducing the contact resistance between particles, and improving the conductivity of the electrode. At the same time, lithium polyacrylate, as a binder, can firmly bond the active material particles together, prevent the pulverization and shedding of particles caused by volume changes during charging and discharging, and improve the structural stability and mechanical strength of the electrode. Therefore, the synergistic effect of carbon nanotubes and lithium polyacrylate can optimize the conductive network and structural integrity of the electrode from a macroscopic perspective, and further improve the comprehensive performance of the battery positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is a schematic structural diagram of a positive electrode in one embodiment of the present invention;

[0046] Figure 2 Schematic diagram of the structure of a composite current collector of a positive electrode in one embodiment of the present invention;

[0047] Figure 3 Schematic diagram of the structure of a composite current collector of a positive electrode in another embodiment of the present invention.

[0048] In the figure: 1. composite current collector; 11. aluminum foil layer; 12. composite foam aluminum layer; 121. first foam aluminum; 122. second foam aluminum; 123. third foam aluminum; 13. carbon nanocoating; 2. positive electrode active material coating. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Please see attached Figure 1~2 The present invention provides a high-rate and long-cycle-life battery positive electrode, comprising a composite current collector 1 and a positive electrode active material coating 2 coated on at least one surface of the composite current collector 1; the positive electrode active material coating 2 comprises a positive electrode active material, carbon nanotubes and lithium polyacrylate; the mass ratio of the positive electrode active material, the carbon nanotubes and lithium polyacrylate is (90~99.5):(0.2~5):(0.3~5), and the positive electrode active material comprises lithium iron phosphate particles, a fast ion conductor coating layer coated on the outer surface of the lithium iron phosphate particles, and a carbon coating layer coated on the outer surface of the fast ion conductor coating layer.

[0051] Among them, the present invention constructs a fast ion conductor coating layer and a carbon coating layer on the surface of the lithium iron phosphate particles of the positive electrode. The fast ion conductor coating layer can not only effectively block the contact between the positive electrode material and the electrolyte, thereby greatly reducing the dissolution of transition metals and the occurrence of side reactions between the electrode and the electrolyte; it also provides a channel for rapid diffusion and conduction of lithium ions, promotes the rapid migration and insertion and extraction of lithium ions, and improves the ionic conductivity of the lithium iron phosphate material; while the carbon coating layer can improve the electronic conductivity of the material and accelerate the charge transfer dynamics. The synergistic effect of the two coating layers effectively overcomes the inherent conductivity defects of lithium iron phosphate and effectively improves the rate and cycle stability of the positive electrode.

[0052] In addition, the positive electrode active material coating 2 of the present invention further optimizes the conductive network and structural stability of the material by adding carbon nanotubes and lithium polyacrylate to the positive electrode active material. Among them, carbon nanotubes have excellent conductivity and mechanical strength, and can build efficient electron transmission channels between active material particles; while lithium polyacrylate can be used as a binder to improve the structural integrity and mechanical strength of the material and prevent the active material from pulverizing and falling off during long-term circulation.

[0053] In summary, the high-rate and long-cycle-life battery positive electrode proposed in the present invention constructs a fast ion conductor coating layer and a carbon coating layer on the surface of the lithium iron phosphate material, optimizes the conductive network and microstructure of the positive electrode active material, and combines a composite foam aluminum current collector with a hierarchical structure design, thereby effectively overcoming the shortcomings of the prior art and achieving a comprehensive improvement in the battery positive electrode rate performance, cycle stability and energy density.

[0054] In one embodiment of the present application, the particle size of the positive electrode active material particles is 0.1-1.5 μm. The present invention controls the particle size of the positive electrode active material to 0.1-1.5 μm, which can significantly increase the specific surface area of ​​the material, shorten the ion diffusion path, and thus improve the rate performance of the material.

[0055] Among them, the particle size of the positive electrode active material is one of the important factors affecting its electrochemical performance. Reducing the particle size can significantly increase the specific surface area of ​​the material, increase the contact area with the electrolyte, and promote the charge transfer dynamics. At the same time, the reduction in particle size also means a shortening of the ion diffusion path, and lithium ions can be embedded in and out of the active material particles faster, improving the rate performance of the material. However, too small a particle size may also bring some problems, such as an increase in side reactions caused by an excessively large specific surface area and serious agglomeration. Therefore, the present invention preferably controls the particle size within the range of 0.1~1.5μm, while increasing the specific surface area and shortening the diffusion path, avoiding the negative impact of too small a particle size, and achieving the optimization of rate performance.

[0056] In one embodiment of the present application, the peak intensity ratio ID / IG of the D peak and the G peak of the carbon coating layer in the Raman spectrum satisfies the relationship: 0.2≤ID / IG≤0.6. The graphitization degree of the carbon coating layer is controlled within the range of ID / IG of 0.2 to 0.6, which can ensure good conductivity while avoiding structural instability caused by excessive graphitization; a moderate degree of graphitization is conducive to the formation of an ordered carbon layer structure, providing more electron transmission channels, reducing the electron migration barrier, and thus greatly improving the conductivity of the active material.

[0057] Among them, the intensity ratio ID / IG of the D peak (amorphous carbon) and the G peak (graphitized carbon) in the Raman spectrum can characterize the degree of graphitization of the carbon material; the lower the ID / IG value, the lower the amorphous carbon content in the carbon layer, the higher the degree of graphitization, and the better the conductivity; controlling ID / IG at 0.2~0.6 means that graphitized carbon dominates the carbon coating layer and the amorphous carbon content is low. Therefore, the overall conductivity of the active material is greatly improved, the electron transmission is smoother, and the specific capacity of the active material is more fully utilized.

[0058] In one embodiment of the present application, the preparation method of the positive electrode active material is as follows:

[0059] 1) Mixing a raw material of a fast ion conductor with hydrogen peroxide, reflux at 50-60° C. for 5-10 hours, reflux at 70-90° C. for 1-5 hours, and reflux at 90-100° C. for 0.5-3 hours, then adding anhydrous ethanol, heating and reflux again to obtain a polyoxometalate; wherein the raw material of the fast ion conductor is a transition metal element and / or a transition metal compound;

[0060] 2) dispersing FePO4 in polyoxometalate, drying and heat treating the FePO4 at a temperature of 300 to 600° C. for 2 to 6 hours to obtain FePO4 coated with a fast ion conductor;

[0061] 3) mixing the fast ion conductor coated FePO4, Li2CO3 and glucose in a mass ratio of (1-2):(4-6):(1-2), adding water, adjusting the solid content to 20%-40 wt %, and fully stirring and dispersing for 1-2 hours to obtain a mixed material;

[0062] 4) spray drying the mixed material in step 3), and adjusting the inlet temperature of the spray drying equipment to 200-240° C., the outlet temperature to 100-120° C., and the feed rate to 80 kg / h to obtain a dried material;

[0063] 5) The spray-dried material is loaded into a mold, compacted into blocks using a hydraulic press, loaded into a sagger, and then transferred to a push plate furnace for sintering;

[0064] 6) Heat up the push plate furnace first, pass nitrogen, reach the atmosphere requirement of less than 100ppm, push the sagger into the push plate furnace, and sinter according to the heating stage of 300~550℃, 4~6h; constant temperature stage of 750℃, 8~10h; cooling stage of 6~8h, and discharge;

[0065] 7) Grind the material fired in the push plate furnace to obtain a positive electrode active material with a particle size of 0.1~1.5μm.

[0066] Among them, the present invention adopts a liquid phase method to prepare a fast ion conductor coating layer, and a coating layer that is uniform and dense and tightly combined with the substrate can be obtained. Compared with the traditional solid phase method, the liquid phase coating process is more controllable, and the thickness and morphology of the coating layer can be accurately regulated, so as to maximize the synergistic effect of the composite modification. Specifically, the traditional solid phase mixing method for preparing a fast ion conductor coating layer is often difficult to achieve precise control of the coating layer composition and thickness, and the coating layer has a weak binding force with the lithium iron phosphate particles, and is easy to fall off during the charge and discharge process, resulting in poor modification effect. The liquid phase coating method used in the present invention can finely control the composition, thickness and morphology of the fast ion conductor coating layer by regulating the concentration of the precursor solution, the reaction temperature and time and other parameters, and obtain a uniform and dense coating layer that is tightly combined with the substrate. This high-quality coating layer can maximize the role of the fast ion conductor, provide a more efficient ion transmission channel, and also have better structural stability, and can withstand long-term charge and discharge cycles without falling off, thereby ensuring the durability of the composite modification effect.

[0067] In one embodiment of the present application, in step 1), the transition metal element is one or more of W, Mo, Ti, Nb, Ta and Ir; the transition metal compound is one or more of ammonium tungstate, ammonium metatungstate, tungstic acid, tungsten hexachloride, sodium tungstate dihydrate, ammonium molybdate, molybdenum hexachloride, sodium molybdate, tetrabutyl titanate, titanium tetraisopropoxide, titanium tetrachloride, niobium nitrate and niobium chloride. The present invention can adjust the chemical composition of the coating layer by optimizing the raw materials of the fast ion conductor, introduce metal ions with high mobility, and improve the intrinsic ionic conductivity of the coating layer.

[0068] In one embodiment of the present application, in step 1), the heating reflux temperature after adding anhydrous ethanol is 40 to 60° C., and the reflux time is 15 to 30 hours. By optimizing the preparation process parameters of the positive electrode active material, the composition and microstructure of the fast ion conductor coating layer can be finely controlled to further enhance the composite modification effect.

[0069] In one embodiment of the present application, in step 1), the mass fraction of hydrogen peroxide is 10-30%; the mass ratio of anhydrous ethanol to hydrogen peroxide is 1:(0.5-2); the mass ratio of polyoxometallic acid to positive electrode active material is (0.1-5):100.

[0070] In one embodiment of the present application, the positive electrode active material coating 2 also includes 1,3,5-tri(4-carboxyphenyl)benzene. By adding 1,3,5-tri(4-carboxyphenyl)benzene to the positive electrode active material coating, it can form coordination bonds with the active substance in the pores of the foamed aluminum to achieve connectivity of the internal structure, which is beneficial to improving the conductive performance, strengthening the internal support structure of the foamed aluminum, and enhancing the bending resistance of the positive electrode sheet. At the same time, the binding effect of 1,3,5-tri(4-carboxyphenyl)benzene on the active substance can also reduce the generation of free active substances during the use of the battery and improve the battery cycle performance.

[0071] Specifically, adding 1,3,5-tris(4-carboxyphenyl)benzene to the positive electrode active material coating has at least the following advantages:

[0072] 1) The center of 1,3,5-tri(4-carboxyphenyl)benzene is a benzene ring, and three 4-carboxyphenyl groups are evenly modified at the 1,3,5 positions of the central benzene ring. This symmetrical three-dimensional spatial structure is conducive to the formation of a uniform and stable metal organic framework; the three-dimensional structure of 1,3,5-tri(4-carboxyphenyl)benzene can provide more coordination sites and steric hindrance, forming a more three-dimensional cross-linked network and enhancing the internal support of foam aluminum. 2) 1,3,5-tri(4-carboxyphenyl)benzene contains three free carboxyl groups, which can form coordination bonds with the central ions of multiple positive electrode active materials (such as transition metal oxides); each 1,3,5-tri(4-carboxyphenyl)benzene molecule can connect three active material particles to form a "Y"-type coordination structure; this multi-coordination site design can increase the connectivity of active materials, promote electron and ion transport, and improve conductivity.

[0073] 3) The three 4-carboxyphenyl groups of 1,3,5-tri(4-carboxyphenyl)benzene present a unique spatial orientation. After forming a metal-organic framework, they can form a staggered three-dimensional barrier structure in the pores of foamed aluminum. On the one hand, this spatial steric hindrance effect can increase the mechanical strength of the positive electrode material and improve its bending resistance. On the other hand, it can also effectively inhibit the shedding and dissolution of active substances during the battery cycle, reduce the generation of free active substances, and improve the cycle stability of the battery.

[0074] 4) The central benzene ring of 1,3,5-tri(4-carboxyphenyl)benzene and the three 4-carboxyphenyl groups are connected by rigid σ bonds, and the conformation of the entire molecule is relatively stable. This rigid structure is beneficial to maintaining the structural integrity of the metal organic framework in the complex and porous internal environment of foamed aluminum, and avoiding the collapse of the framework caused by changes in the ligand conformation. At the same time, the rigid structure can also buffer the volume changes during the charge and discharge process of the battery and maintain the structural stability of the positive electrode material. 5) In addition, the benzene ring structure in 1,3,5-tri(4-carboxyphenyl)benzene has good chemical stability and electrochemical stability; within the potential window of battery operation, 1,3,5-tri(4-carboxyphenyl)benzene will not undergo redox reactions, nor will it have side reactions with the electrolyte; this stable electrochemical behavior can ensure that 1,3,5-tri(4-carboxyphenyl)benzene always plays a coordination connection role in long-term cycles, maintain the structural integrity and conductive network of the positive electrode material, and extend the service life of the battery.

[0075] In one embodiment of the present application, the composite current collector 1 includes an aluminum foil layer 11 and a composite aluminum foam layer 12 arranged on the aluminum foil layer 11, the composite aluminum foam layer 12 consists of three layers of aluminum foams with different densities, different porosities and different thicknesses; the composite current collector 1 is connected to a positive electrode tab; the composite aluminum foam layer 12 includes a first aluminum foam 121, a second aluminum foam 122 and a third aluminum foam 123 arranged in sequence from the inside to the outside, and the density ρ1 of the first aluminum foam 121, the density ρ2 of the second aluminum foam 122 and the density ρ3 of the third aluminum foam 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first aluminum foam 121, the porosity φ2 of the second aluminum foam 122 and the porosity φ3 of the third aluminum foam 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first aluminum foam 121, the thickness h2 of the second aluminum foam 122 and the thickness h3 of the third aluminum foam 123 satisfy the relationship: h1<h2<h3.

[0076] The composite aluminum foam current collector of the present invention adopts a hierarchical structure design, which can significantly improve the mechanical strength and structural stability of the current collector while ensuring a high specific surface area and conductivity. The presence of the inner layer of high-density aluminum foam can effectively bear the mechanical load of the current collector and prevent deformation and fracture; while the outer layer of low-density aluminum foam can provide a larger specific surface area and porosity, promoting electrolyte infiltration and ion transmission. Therefore, the hierarchical structure design effectively balances the multiple performance requirements of the current collector and significantly improves the comprehensive performance of the battery positive electrode.

[0077] Among them, although the traditional single-layer aluminum foam current collector has a high specific surface area and porosity, its mechanical strength and structural stability are poor; it is difficult to withstand the stress impact during battery assembly and charging and discharging; it is easy to deform or break, resulting in problems such as active material shedding and increased interface impedance. After the hierarchical structure design is adopted in the present invention, the inner layer of high-density aluminum foam can be used as a mechanical support layer to provide sufficient mechanical strength and rigidity to prevent the current collector from deforming and breaking; the middle layer has a moderate density and plays a transition and connection role; the outer layer of low-density aluminum foam can maximize the specific surface area and porosity, promote electrolyte infiltration and ion transfer, and reduce interface impedance. At the same time, this hierarchical structure can also achieve a gradient distribution of stress to avoid local damage caused by stress concentration. Therefore, the hierarchical structure aluminum foam current collector can ensure high specific surface area and conductivity while taking into account mechanical strength and structural stability, thereby improving the applicability and reliability of the current collector in the positive electrode of the battery.

[0078] In summary, the composite current collector 1 of the present invention comprises an aluminum foil layer 11 and a composite aluminum foam layer 12, wherein the composite aluminum foam layer 12 is composed of three layers of aluminum foams with different densities, different porosities and different thicknesses, which are distributed in a gradient manner. This structure has the following outstanding advantages:

[0079] 1) High specific surface area: The gradient-distributed composite foam aluminum layer 12 has a high specific surface area and a three-dimensional porous structure as a whole. The outer layer of low-density, high-porosity and thicker foam aluminum can load more active substances, improve the utilization rate of active materials, and increase battery capacity.

[0080] 2) High conductivity: The outer layer of aluminum foam is in direct contact with the active material, and its loose and porous structure is conducive to the infiltration of the electrolyte and the rapid transmission of ions, thereby reducing the interface resistance. The inner layer of aluminum foam with high density and low porosity can provide an effective electron transmission channel, thus ensuring the high conductivity of the current collector.

[0081] 3) High mechanical strength: The inner layer of high-density, low-porosity and thin aluminum foam can provide sufficient mechanical support to ensure the structural integrity of the current collector; the middle layer has moderate density and porosity, which plays a transition and buffering role and improves the mechanical stability of the current collector.

[0082] 4) High structural stability: The gradient structure design can achieve layer-by-layer transmission and uniform distribution of stress. The outer layer of low-density, high-porosity and thick aluminum foam can effectively absorb and buffer the stress generated during the battery charging and discharging process, avoid stress concentration leading to local deformation or fracture of the current collector, and extend the cycle life of the battery.

[0083] In one embodiment of the present application, the density ρ1 of the first foam aluminum 121 is 0.5-0.9 g / cm³, preferably 0.7 g / cm³, the density ρ2 of the second foam aluminum 122 is 0.3-0.5 g / cm³, preferably 0.4 g / cm³, and the density ρ3 of the third foam aluminum 123 is 0.1-0.3 g / cm³, preferably 0.2 g / cm³; the porosity φ1 of the first foam aluminum 121 is 50-70%, preferably 60 %, the porosity φ2 of the second foam aluminum 122 is 70-85%, preferably 80%, the porosity φ3 of the third foam aluminum 123 is 85-95%, preferably 90%; the thickness h1 of the first foam aluminum 121 is 0.5-1μm, the thickness h2 of the second foam aluminum 122 is 1-2μm, and the thickness h3 of the third foam aluminum 123 is 2-4μm; the thickness h4 of the aluminum foil layer 11 is 0.5-1μm; the total thickness of the composite current collector 1 is 4-8μm.

[0084] By rationally designing the above parameters, the specific surface area and conductivity of the current collector can be maximized while ensuring the mechanical strength and structural stability. For example, by appropriately reducing the density of the inner layer of aluminum foam and increasing the porosity, the specific surface area can be increased while ensuring the mechanical strength, promoting electrolyte infiltration and ion transport; and by appropriately reducing the thickness and pore size of the outer layer of aluminum foam, a higher specific surface area and a smaller pore size can be obtained, the loading amount of active materials can be increased and the ion diffusion path can be shortened. At the same time, optimizing the thickness ratio of each layer of aluminum foam can achieve the best balance between mechanical strength and specific surface area. Therefore, by rationally designing the structural parameters of the composite aluminum foam current collector, the conductivity and specific surface area of ​​the current collector can be maximized while ensuring mechanical stability, thereby improving the rate performance and cycle performance of the positive electrode of the battery. In addition, the total thickness of the positive composite current collector 1 of the present invention is controlled within the ultra-thin range of 4-8 μm, which can significantly reduce the thickness and mass of the current collector compared with the traditional aluminum foil current collector, further improve the energy density and specific power of the battery, and is conducive to the miniaturization and lightweight design of the battery. In addition, the thickness of each aluminum foam layer will also directly affect the performance of the battery; if the thickness of each aluminum foam layer is insufficient, the active material particles may be squeezed out of the pores or destroyed under pressure, which will reduce the overall performance of the pole piece, resulting in a decrease in the rate performance and cycle life of the battery; on the other hand, if the thickness of each aluminum foam layer is too large, the proportion of inactive materials will increase, thereby reducing the energy density of the battery. Therefore, controlling the appropriate thickness of each aluminum foam layer is crucial to optimizing the performance of lithium-ion batteries.

[0085] In one embodiment of the present application, the pore size d1 of the first aluminum foam 121, the pore size d2 of the second aluminum foam 122, and the pore size d3 of the third aluminum foam 123 satisfy the relationship: d1<d2<d3; the pore size d1 of the first aluminum foam 121 is 1~5μm, preferably 3μm, the pore size d2 of the second aluminum foam 122 is 5~10μm, preferably 8μm, and the pore size d3 of the third aluminum foam 123 is 10~15μm, preferably 13μm. The horn-shaped distribution of the pore size gradient can form a multi-level porous structure that is conducive to the diffusion of lithium ions and the embedding of active substances. The large pore size of the outer layer is conducive to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance, maintain the stability of the electrode structure, and improve the rate performance and cycle stability of the battery. In addition, the size of the pores has a decisive influence on the permeability of the slurry. If the pore size is too small, the slurry may not be able to effectively fill the pores due to the surface tension of the slurry, which will hinder the uniform distribution of the active material and affect the performance of the electrode. On the contrary, if the pore size is too large, the slurry will easily overfill the pores, resulting in an increase in the surface density. During the drying process, this overfilling may cause local cracks, further affecting the rate performance of the battery. Therefore, choosing the right pore size is crucial to ensuring the quality of the electrode and battery performance.

[0086] In one embodiment according to the present application, Figure 3 As shown, the surface of the composite aluminum foam layer 12 is also provided with a carbon nano coating 13, and the thickness of the carbon nano coating 13 is 10-20nm. Coating the carbon nano coating 13 on the surface of the composite aluminum foam can further improve the conductivity and corrosion resistance of the current collector. The carbon nano coating 13 is tightly combined with the aluminum foam matrix to form a dense and uniform conductive protective layer on the surface of the current collector, which effectively reduces the interface resistance, while also improving the chemical stability of the current collector in the electrolyte environment, and extending the cycle life of the battery. In addition, the appropriate thickness of the carbon nano coating 13 can avoid the pore blockage or increase of the interface impedance caused by the coating being too thick.

[0087] Among them, although foamed aluminum has excellent conductivity and specific surface area, its surface may be corroded by the electrolyte, generating an insulating aluminum oxide passivation layer, resulting in increased interface impedance and battery performance attenuation. By coating a layer of carbon nano coating 13 on the surface of foamed aluminum, the direct contact between foamed aluminum and the electrolyte can be effectively isolated to prevent the occurrence of corrosion reactions. At the same time, the carbon nano coating 13 itself has excellent conductivity, and can form a uniform and dense conductive network on the surface of foamed aluminum, reduce interface resistance, and improve the conductivity of the current collector. In addition, the carbon nano coating 13 also has excellent chemical stability, can be stably present in the electrolyte environment for a long time, delay the attenuation of the current collector performance, and improve the cycle life of the battery. Therefore, the introduction of carbon nano coating 13 can further optimize the performance of the composite foamed aluminum current collector from the two aspects of conductivity and corrosion resistance, and provide a better current collector material for the positive electrode of high-performance lithium-ion batteries.

[0088] In addition, the present invention also provides a method for preparing the above-mentioned high-rate and long-cycle-life battery positive electrode, comprising the following steps:

[0089] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;

[0090] a. The first foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15-25):1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the aluminum powder is 0.1-0.4μm, and the particle size of the urea is 0.2-0.5μm;

[0091] b. The second foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the aluminum powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm;

[0092] c. The third foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the aluminum powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm;

[0093] 2) preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process;

[0094] 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer;

[0095] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried;

[0096] 5) Dispersing the positive electrode active material, carbon nanotubes and lithium polyacrylate in N-methylpyrrolidone in a mass ratio of (90-99.5):(0.2-5):(0.3-5), and stirring evenly to obtain a positive electrode active material coating slurry;

[0097] 6) coating the positive electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the battery positive electrode.

[0098] Among them, the positive electrode current collector preparation method of the present invention adopts a process route of gradient slurry ratio and layer-by-layer coating and sintering, which is simple to operate and easy to control. By adjusting the slurry components, solid content, particle size and coating process parameters, the microstructural parameters such as density, porosity, thickness and pore size of the composite foam aluminum can be accurately controlled to ensure the consistency and repeatability of the current collector performance. In addition, by controlling the particle size of aluminum powder and urea pore former in different layers of slurry, the pore size and porosity of the foam aluminum can be effectively controlled to ensure the formation of a gradient structure, while avoiding problems such as incomplete sintering or pore collapse caused by excessive or small particle size. Therefore, the positive electrode preparation process proposed by the present invention is simple and controllable to operate, and is easy to promote and apply in industrialization.

[0099] In one embodiment of the present application, step 4) further includes surface modification of the composite current collector 1 obtained after cooling, depositing a 10-20 nm thick carbon nano coating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 100-150°C and a rolling rate of 5-10%. The introduction of surface modification and hot rolling processes can further improve the conductivity and bonding strength of the composite current collector 1, and improve the interface compatibility and mechanical properties between the current collector and the active material coating.

[0100] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0101] Example 1

[0102] Preparation of positive electrode:

[0103] The positive electrode of the battery of this embodiment includes a composite current collector 1, a positive electrode active material coating 2 coated on a surface of the composite current collector 1; the positive electrode active material coating 2 includes positive electrode active material, carbon nanotubes and lithium polyacrylate; the mass ratio of the positive electrode active material, carbon nanotubes and lithium polyacrylate is 96:2:2, and the positive electrode active material includes lithium iron phosphate particles, a fast ion conductor coating layer coated on the outer surface of the lithium iron phosphate particles, and a carbon coating layer coated on the outer surface of the fast ion conductor coating layer. The particle size of the positive electrode active material particles is 0.5 μm.

[0104] The preparation method of the positive electrode active material is as follows:

[0105] 1) Mix the raw materials of the fast ion conductor with hydrogen peroxide, reflux at 55°C for 8h, reflux at 80°C for 3h, and reflux at 95°C for 1.5h, then add anhydrous ethanol, heat and reflux again, the heating reflux temperature is 50°C, and the reflux time is 20h to obtain polymetallic oxoacid; wherein the raw materials of the fast ion conductor are W and ammonium tungstate; the mass fraction of hydrogen peroxide is 20%; the mass ratio of anhydrous ethanol to hydrogen peroxide is 1:1; the mass ratio of polymetallic oxoacid to positive electrode active material is 1:100.

[0106] 2) dispersing FePO4 in the polyoxometallic acid, drying and heat treating the FePO4 at a temperature of 450° C. for 4 hours to obtain FePO4 coated with a fast ion conductor;

[0107] 3) The fast ion conductor coated FePO4, Li2CO3 and glucose were mixed in a mass ratio of 1:4:1, water was added, the solid content was adjusted to 30 wt %, and the mixture was fully stirred and dispersed for 1.5 h to obtain a mixed material;

[0108] 4) spray drying the mixed material in step 3), and adjusting the inlet temperature of the spray drying equipment to 230° C., the outlet temperature to 110° C., and the feed rate to 80 kg / h to obtain a dried material;

[0109] 5) The spray-dried material is loaded into a mold, compacted into blocks using a hydraulic press, loaded into a sagger, and then transferred to a push plate furnace for sintering;

[0110] 6) Heat up the push plate furnace first, pass nitrogen, reach the atmosphere requirement of less than 100ppm, push the sagger into the push plate furnace, and sinter according to the heating stage of 300~550℃, 5h; constant temperature stage of 750℃, 9h; cooling stage of 7h, and then discharge;

[0111] 7) Grind the material fired in the push plate furnace to obtain a positive electrode active material with a particle size of 0.5 μm.

[0112] The composite current collector 1 includes an aluminum foil layer 11 and a composite aluminum foam layer 12 disposed on the aluminum foil layer 11, wherein the composite aluminum foam layer 12 is composed of three layers of aluminum foams with different densities, different porosities and different thicknesses; the composite current collector 1 is connected to a positive electrode tab;

[0113] The composite foam aluminum layer 12 includes a first foam aluminum 121, a second foam aluminum 122 and a third foam aluminum 123 which are arranged in sequence from the inside to the outside. The density ρ1 of the first foam aluminum 121, the density ρ2 of the second foam aluminum 122 and the density ρ3 of the third foam aluminum 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first foam aluminum 121, the porosity φ2 of the second foam aluminum 122 and the porosity φ3 of the third foam aluminum 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first foam aluminum 121, the thickness h2 of the second foam aluminum 122 and the thickness h3 of the third foam aluminum 123 satisfy the relationship: h1<h2<h3.

[0114] Specifically, in this embodiment, the density ρ1 of the first aluminum foam 121 is 0.7g / cm³, the density ρ2 of the second aluminum foam 122 is 0.4g / cm³, and the density ρ3 of the third aluminum foam 123 is 0.2g / cm³. The porosity φ1 of the first aluminum foam 121 is 60%, the porosity φ2 of the second aluminum foam 122 is 80%, and the porosity φ3 of the third aluminum foam 123 is 90%. The thickness h1 of the first aluminum foam 121 is 0.5μm, the thickness h2 of the second aluminum foam 122 is 1.5μm, and the thickness h3 of the third aluminum foam 123 is 3μm; the thickness h4 of the aluminum foil layer 11 is 1μm; the total thickness of the composite current collector 1 is 6μm.

[0115] The preparation method of the positive electrode sheet is as follows:

[0116] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;

[0117] a. The first foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:20:1, anhydrous ethanol is added, and the solid content is adjusted to 40wt%; wherein the particle size of the aluminum powder is 0.2μm, and the particle size of the urea is 0.4μm;

[0118] b. The second foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:30:1, anhydrous ethanol is added, and the solid content is adjusted to 25wt%; wherein the particle size of the aluminum powder is 0.5μm, and the particle size of the urea is 0.8μm;

[0119] c. The third foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:50:1, anhydrous ethanol is added, and the solid content is adjusted to 10wt%; wherein the particle size of the aluminum powder is 1μm, and the particle size of the urea is 1.5μm;

[0120] 2) Preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence. During the coating process, spray a small amount of anhydrous ethanol on the surface of each layer of slurry to promote the bonding and fusion between the layers;

[0121] 3) Place the coated aluminum foil in a vacuum sintering furnace, and heat it to 700°C at a heating rate of 3°C / min under the protection of an argon atmosphere, and keep it at that temperature for 1 hour, so that the aluminum powder is sintered to form a gradient porous structure, and at the same time, urea is decomposed to produce gas to form a gradient aluminum foam layer;

[0122] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried at a temperature of 70°C for 0.5 hours;

[0123] 5) dispersing the positive electrode active material, carbon nanotubes and lithium polyacrylate in N-methylpyrrolidone at a mass ratio of 96:2:2, and stirring evenly to obtain a positive electrode active material coating slurry;

[0124] 6) Coating the positive electrode active material coating slurry on one surface of the composite current collector and drying it to obtain a positive electrode sheet of the battery.

[0125] Preparation of negative electrode sheet:

[0126] Hard carbon, carbon black and aqueous carboxymethyl cellulose are dispersed in water at a mass ratio of 95:2:3 to form a uniformly dispersed slurry, the slurry is evenly coated on the surface of the current collector copper foil, and then transferred to a vacuum drying oven for complete drying to obtain a negative electrode sheet.

[0127] Preparation of electrolyte:

[0128] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1, and then fluoroethylene carbonate (FEC) is added at a volume percentage of 5%. Then, fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a concentration ratio of 1 mol / L to prepare an electrolyte.

[0129] Preparation of isolation film: A PET / PP composite film with a thickness of 15 microns was selected.

[0130] Preparation of lithium-ion batteries:

[0131] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and the electrolyte is added, and a lithium-ion battery is assembled according to conventional processes.

[0132] Example 2

[0133] Different from Example 1, in the composite current collector 1 of the positive electrode of this embodiment, the surface of the composite foam aluminum layer 12 is further provided with a carbon nano coating 13, and the thickness of the carbon nano coating 13 is 15 nm.

[0134] In addition, step 4) of the preparation method of the positive electrode plate also includes surface modification of the composite current collector 1 obtained after cooling, depositing a 15 nm thick carbon nanocoating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 120° C. and a rolling rate of 8%.

[0135] The rest is the same as in Example 1 and will not be described again here.

[0136] Example 3

[0137] Different from Example 1, in the composite current collector 1 of the positive electrode of this embodiment, the pore size d1 of the first foam aluminum 121, the pore size d2 of the second foam aluminum 122 and the pore size d3 of the third foam aluminum 123 satisfy the relationship: d1<d2<d3.

[0138] Specifically, in this embodiment, the pore size d1 of the first foam aluminum 121 is 3 μm, the pore size d2 of the second foam aluminum 122 is 8 μm, and the pore size d3 of the third foam aluminum 123 is 13 μm.

[0139] In addition, in step 1) of the preparation method of the positive electrode plate, in the first foam aluminum 121 layer slurry, the particle size of the aluminum powder is 0.1 μm, and the particle size of the urea is 0.3 μm; in the second foam aluminum 122 layer slurry, the particle size of the aluminum powder is 0.5 μm, and the particle size of the urea is 0.8 μm; in the third foam aluminum 123 layer slurry, the particle size of the aluminum powder is 1 μm, and the particle size of the urea is 1.3 μm.

[0140] The rest is the same as in Example 1 and will not be described again here.

[0141] Example 4

[0142] Different from Example 1, the positive electrode active material coating 2 of the positive electrode of this embodiment includes positive electrode active material, carbon nanotubes, lithium polyacrylate and 1,3,5-tris(4-carboxyphenyl)benzene; the mass ratio of positive electrode active material, carbon nanotubes, lithium polyacrylate and 1,3,5-tris(4-carboxyphenyl)benzene is 96:2:1.5:0.5.

[0143] The rest is the same as in Example 1 and will not be described again here.

[0144] Comparative Example 1

[0145] Different from Example 1, the positive electrode active material of this comparative example is lithium iron phosphate, and no modification or coating is performed.

[0146] The rest is the same as in Example 1 and will not be described again here.

[0147] Comparative Example 2

[0148] Different from Example 1, the positive electrode active material of this comparative example is lithium iron phosphate, and the surface of the lithium iron phosphate is only coated with carbon without being coated with a fast ion conductor.

[0149] The rest is the same as in Example 1 and will not be described again here.

[0150] Comparative Example 3

[0151] Different from Example 1, the positive electrode current collector of this comparative example adopts an aluminum foil current collector with a thickness of 10 μm.

[0152] The rest is the same as in Example 1 and will not be described again here.

[0153] Comparative Example 4

[0154] Different from Example 1, the current collector of the positive electrode of this comparative example adopts a single-layer foam aluminum current collector, and the foam aluminum current collector has a density of 0.5 g / cm³, a porosity of 90%, and a thickness of 10 μm.

[0155] The rest is the same as in Example 1 and will not be described again here.

[0156] The positive electrode sheets of the above embodiments and comparative examples were tested for ductility and stability, and the rate performance and cycle performance of 1Ah lithium-ion batteries made from the positive electrode sheets were tested. At the same time, the DCR and battery internal resistance of each positive active material powder were tested. The test results are shown in Table 1.

[0157] Ductility test: Under the same pressure (20 tons), the positive electrode sheets prepared in the embodiment and the comparative example were rolled to observe whether there was brittle fracture or cracking on the surface of the sheet. If any of the above phenomena occurred, it means that the ductility is poor.

[0158] Stability test: 10 positive electrode sheets prepared in the embodiments and comparative examples were respectively subjected to 90-degree folding and twisting experiments to observe the condition of the active materials at the folded or twisted parts. If any active materials fell off or broke, it indicated that the structural stability was poor.

[0159] Table 1

[0160] The test results of Table 1 above are analyzed as follows:

[0161] By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that compared with the existing method of directly using lithium iron phosphate as the positive electrode active material or only using lithium iron phosphate modified by conventional carbon coating as the positive electrode active material, the present invention uses the positive electrode active material formed by first coating the outer surface of lithium iron phosphate particles with a fast ion conductor layer and then coating the carbon layer, which can effectively reduce the internal resistance of the battery and improve the rate performance and cycle life of the battery. Because after the introduction of the fast ion conductor coating layer, on the one hand, the fast ion conductor material itself has a high ionic conductivity, which can provide a fast transmission channel for lithium ions; on the other hand, an atomic-scale transition zone is formed at the interface between the fast ion conductor layer and the lithium iron phosphate particles, which is conducive to the rapid migration of lithium ions at the interface and reduces the interface impedance; in addition, the fast ion conductor coating layer can also effectively block the contact between the positive electrode material and the electrolyte, thereby greatly reducing the dissolution of the transition metal and the occurrence of side reactions between the electrode and the electrolyte; therefore, the fast ion conductor coating layer can significantly improve the ionic conductivity of the lithium iron phosphate material, improve the rate performance and cycle performance. At the same time, the introduction of the carbon coating can improve the electronic conductivity of the material, accelerate the electron transfer dynamics, and increase the charge and discharge rate of the material.

[0162] By comparing Example 1 with Comparative Examples 3 to 4, it can be seen that compared with the positive electrode prepared by the existing copper foil current collector or the single-layer foam aluminum current collector, the positive electrode of the present invention has better ductility, structural stability and lower contact resistance, because the positive electrode active material of the present invention has been infiltrated into the three-dimensional structure of the composite foam aluminum, and the gradient density composite foam aluminum itself has good flexibility, so it has a better retention effect on the active material infiltrated therein, thereby ensuring that the positive electrode prepared by the composite foam aluminum has better deformation resistance and structural stability during the processing process and the use of the battery, and can effectively prevent the positive electrode from brittle fracture or cracking, and effectively reduce the contact resistance, so the lithium ion battery prepared by the positive electrode of the present invention has higher rate performance and cycle life.

[0163] By comparing Example 1 and Example 2, it can be seen that when the surface of the composite foam aluminum layer of the positive electrode is further provided with a carbon nanocoating for surface modification, and the surface-modified composite current collector is further subjected to hot rolling treatment, the conductivity of the pole piece can be further improved, the interface resistance can be reduced, and it is beneficial to further improve the rate performance and cycle life of the battery.

[0164] By comparing Example 1 and Example 3, it can be seen that when the composite foam aluminum layer of the positive electrode adopts a pore size gradient distribution, a multi-level porous structure that is beneficial to the diffusion of lithium ions and the embedding of active substances can be formed. The large pore size of the outer layer is beneficial to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance and maintain the stability of the electrode structure. It can ensure that the positive electrode has a high specific surface area and high conductivity while taking into account better mechanical strength and structural stability, thereby further improving the rate performance and cycle life of the battery.

[0165] Comparing Example 1 and Example 4, it can be seen that when 1,3,5-tri(4-carboxyphenyl)benzene is further added to the positive electrode active material coating of the positive electrode, the deformation resistance and structural stability of the positive electrode can be further improved, while reducing the internal resistance of the battery and improving the cycle life of the battery. This is because 1,3,5-tri(4-carboxyphenyl)benzene can form coordination bonds with the active material in the pores of the foamed aluminum to achieve the connectivity of the internal structure, which is beneficial to the improvement of the conductive performance, and can also enhance the internal support structure of the foamed aluminum and the anti-bending performance of the positive electrode sheet. At the same time, the binding effect of 1,3,5-tri(4-carboxyphenyl)benzene on the active material can also reduce the generation of free active materials during the use of the battery and improve the cycle life of the battery.

[0166] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0167] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A battery positive electrode with high rate and long cycle life, characterized in that: It includes a composite current collector and a positive electrode active material coating coated on at least one surface of the composite current collector; the positive electrode active material coating includes a positive electrode active material, carbon nanotubes and lithium polyacrylate; the mass ratio of the positive electrode active material, the carbon nanotubes and the lithium polyacrylate is (90~99.5):(0.2~5):(0.3~5), and the positive electrode active material includes lithium iron phosphate particles, a fast ion conductor coating coated on the outer surface of the lithium iron phosphate particles, and a carbon coating coated on the outer surface of the fast ion conductor coating.

2. The high-rate and long-cycle-life battery positive electrode according to claim 1, characterized in that: The particle size of the positive electrode active material particles is 0.1-1.5 μm.

3. The high-rate and long-cycle-life battery positive electrode according to any one of claims 1 to 2, characterized in that: The preparation method of the positive electrode active material is as follows: 1) Mixing a raw material of a fast ion conductor with hydrogen peroxide, reflux at 50-60° C. for 5-10 hours, reflux at 70-90° C. for 1-5 hours, and reflux at 90-100° C. for 0.5-3 hours, then adding anhydrous ethanol, heating and reflux again to obtain a polyoxometalate; wherein the raw material of the fast ion conductor is a transition metal element and / or a transition metal compound; 2) dispersing FePO4 in the polyoxometallic acid, drying and heat treating the FePO4 at a temperature of 300 to 600° C. for 2 to 6 hours to obtain FePO4 coated with a fast ion conductor; 3) mixing the fast ion conductor coated FePO4, Li2CO3 and glucose in a mass ratio of (1-2):(4-6):(1-2), adding water, adjusting the solid content to 20%-40 wt %, and fully stirring and dispersing for 1-2 hours to obtain a mixed material; 4) spray drying the mixed material in step 3), and adjusting the inlet temperature of the spray drying equipment to 200-240° C., the outlet temperature to 100-120° C., and the feed rate to 80 kg / h to obtain a dried material; 5) The spray-dried material is loaded into a mold, compacted into blocks using a hydraulic press, loaded into a sagger, and then transferred to a push plate furnace for sintering; 6) Heat up the push plate furnace first, pass nitrogen, reach the atmosphere requirement of less than 100ppm, push the sagger into the push plate furnace, and sinter according to the heating stage of 300~550℃, 4~6h; constant temperature stage of 750℃, 8~10h; cooling stage of 6~8h, and discharge; 7) Grind the material fired in the push plate furnace to obtain a positive electrode active material with a particle size of 0.1~1.5μm.

4. The high-rate and long-cycle-life battery positive electrode according to claim 3, characterized in that: In step 1), the transition metal element is one or more of W, Mo, Ti, Nb, Ta and Ir; the transition metal compound is one or more of ammonium tungstate, ammonium metatungstate, tungstic acid, tungsten hexachloride, sodium tungstate dihydrate, ammonium molybdate, molybdenum hexachloride, sodium molybdate, tetrabutyl titanate, titanium tetraisopropoxide, titanium tetrachloride, niobium nitrate and niobium chloride.

5. The high-rate and long-cycle-life battery positive electrode according to claim 3, characterized in that: In step 1), the heating reflux temperature after adding anhydrous ethanol is 40 to 60° C., and the reflux time is 15 to 30 hours.

6. The high-rate and long-cycle-life battery positive electrode according to claim 3, characterized in that: In step 1), the mass fraction of the hydrogen peroxide is 10-30%; the mass ratio of the anhydrous ethanol to the hydrogen peroxide is 1:(0.5-2); the mass ratio of the polyoxometallic acid to the positive electrode active material is (0.1-5):

100.

7. The high-rate and long-cycle-life battery positive electrode according to claim 1, characterized in that: The composite current collector includes an aluminum foil layer and a composite aluminum foam layer arranged on the aluminum foil layer, the composite aluminum foam layer includes a first aluminum foam, a second aluminum foam and a third aluminum foam arranged in sequence from the inside to the outside, the density ρ1 of the first aluminum foam, the density ρ2 of the second aluminum foam and the density ρ3 of the third aluminum foam satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first aluminum foam, the porosity φ2 of the second aluminum foam and the porosity φ3 of the third aluminum foam satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first aluminum foam, the thickness h2 of the second aluminum foam and the thickness h3 of the third aluminum foam satisfy the relationship: h1<h2<h3.

8. The high-rate and long-cycle-life battery positive electrode according to claim 7, characterized in that: The density ρ1 of the first foam aluminum is 0.5-0.9g / cm³, the density ρ2 of the second foam aluminum is 0.3-0.5g / cm³, and the density ρ3 of the third foam aluminum is 0.1-0.3g / cm³; the porosity φ1 of the first foam aluminum is 50-70%, the porosity φ2 of the second foam aluminum is 70-85%, and the porosity φ3 of the third foam aluminum is 85-95%; the thickness h1 of the first foam aluminum is 0.5-1μm, the thickness h2 of the second foam aluminum is 1-2μm, and the thickness h3 of the third foam aluminum is 2-4μm; the thickness h4 of the aluminum foil layer is 0.5-1μm; and the total thickness of the composite current collector is 4-8μm.

9. The high-rate and long-cycle-life battery positive electrode according to claim 7 or 8, characterized in that: The pore size d1 of the first foam aluminum, the pore size d2 of the second foam aluminum, and the pore size d3 of the third foam aluminum satisfy the relationship: d1<d2<d3; the pore size d1 of the first foam aluminum is 1~5μm, the pore size d2 of the second foam aluminum is 5~10μm, and the pore size d3 of the third foam aluminum is 10~15μm.

10. A method for preparing a high-rate and long-cycle-life battery positive electrode according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively; a. The first foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (15-25): 1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the aluminum powder is 0.1-0.4μm, and the particle size of the urea is 0.2-0.5μm; b. The second foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the aluminum powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm; c. The third foam aluminum layer slurry is made of aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the aluminum powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm; 2) preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process; 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer; 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried; 5) Dispersing the positive electrode active material, carbon nanotubes and lithium polyacrylate in N-methylpyrrolidone in a mass ratio of (90-99.5):(0.2-5):(0.3-5), and stirring evenly to obtain a positive electrode active material coating slurry; 6) coating the positive electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the battery positive electrode.

Citation Information

Cited By

  • Surface-modified lithium manganese iron phosphate, modification method thereof, positive pole piece and battery

    CN120600807A

  • Surface-modified lithium iron manganese phosphate and modification method thereof, positive electrode sheet and battery

    CN120600807B